Perlindungan Hukum pada Pemenuhan Hak Anak atas Akta Kelahiran - musfianawati musfianawati (Fakultas Hukum Universitas Islam Jember, 2014)
Each and everyone is entitled to of status of civic. Someone child Civic proved with a identity that is act of birth. X'Self identity a child needed to to guarantee child x'self status before law, and ensure that child identity do not manipulation. Government al state in this case Responsibility fulfill children right of act of birth. This matter have been contained in sound some section in Law About Protection of child. But a sound some section in Law about Administration Population, to obtain; get that act of birth do not easy to. Time gone into effect to register in executor institution limited only 60 day. Besides if had been more than 60 day have to obtain; get approval of Functionary Of Institution Executor. And if passing time one year sanctioned which in the form of Fine. At Law About Protection of Child, congeniality of child is someone which not yet eighteen year of is including child in content. Obtaining civic status is human right which must be obtained by Indonesia citizen. Besides limited by registration time and sanctioned which in the form of fine to resident passing registration deadline, government al also not yet executed Law trust About Administration Population about existence of UPTD executor institution in Countryside storey; level and District. For no him of UPTD executor institution as one of the aid duty at Local Government cause resident which is its location far from institution office executor of record-keeping of birth of difficulty to obtain;get its rights. Its meaning of government al state in this case not yet optimal give protection of law to its citizen related to rights obtain;get act of birth